PENGARUH PERBANDINGAN SEMOLINA DAN TEPUNG BERAS MERAH TERHADAP KARAKTERISTIK FETUCINI BASAH - Kholilullah, Ibrahim; Timur Ina, Putu; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 3 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i03.p10, 2020)
This study was conducted to determine the effect of the comparison of semolina and brown rice flour on the characteristics of fresh fettucine and to find out the comparison of semolina and brown rice flour to produce fresh fettucine with the best characteristics. The experimental design used in this study was a completely randomized design (CRD) with various types of comparative treatment of semolina and brown rice flour consisting of 6 treatments namely 100% : 0%, 90% : 0%, 80% : 20%, 70% : 30%, 60% : 40%, and 50% : 50%. All treatments were repeated three times so that they were obtained 18 experimental units. The data obtained were analyzed by variance and if the treatment had significant effect then followed by Duncan test. The results showed that the comparison of semolina and brown rice flour had a significant effect on the ash content, total anthocyanin content, antioxidant activity, texture preferences (hedonic test), and color (scoring test). Ratio of 50% semolina and 50% brown rice flour had the best characteristics that were water content of 67.23%, ash content of 0.36%, total anthocyanin content of 1.05 mg/100g, antioxidant activity of 80.08%, purplish brown color and rather liked, rather chewy and ordinary texture, overall acceptance rather liked.